Social Bacteriophages - Domingo-Calap, Pilar (Microorganisms, 2020)
Despite their simplicity, viruses can display social-like interactions such as cooperation, communication, and cheating. Focusing on bacteriophages, here we review features including viral product sharing, cooperative evasion of antiviral defenses, prudent host exploitation, superinfection exclusion, and inter-phage peptide-mediated signaling. We argue that, in order to achieve a better understanding of these processes, their mechanisms of action need to be considered in the context of social evolution theory, paying special attention to key population-level factors such as genetic relatedness and spatial structure.